The Adaptive Cline at LDH (Lactate Dehydrogenase) in Killifish Fundulus heteroclitus Remains Stationary After 40 Years of Warming Estuaries. (11th March 2014) - Bell, Tina M.; Strand, Allan E.; Sotka, Erik E.
Abstract : Since the 1970s, water temperatures along the Atlantic seaboard of the United States have risen by an average of 0.5 °C in summer months and 2.2 °C in winter months. In response, the distribution and abundance of several nearshore species have changed dramatically, but no study has attempted to document whether estuarine populations have evolved greater thermal tolerance. Here, we re-examine the classic latitudinal cline at lactate dehydrogenase (LDH) in the killifish Fundulus heteroclitus that was originally described by Dennis Powers and associates from samples collected between 1970 and 1972. Laboratory and field evidences indicated that northern and southern isozymes at muscle LDH are locally adapted to cold and warm temperatures, respectively. Despite the potential for evolutionary response at this adaptive locus, we detected no significant shift of the LDH cline from 20 to 30 F. heteroclitus collected at each of 13 locations between the early 1970s and 2010. We conclude that the microevolution of LDH-mediated thermal tolerance has not occurred, that shifts in alleles are too incremental to be distinguished from random processes, or that F. heteroclitus uses phenotypic and genetic mechanisms besides LDH to respond to warmer waters.